The effect of visual merchandising, advertising creativity, e– service quality, and perceived value against the Spotify premium service purchase decision - Aprilia, Putri Windy; Krisnawati, Wenti (Enrichment : Journal of Management, 2023)
The study aims to analyze the influence of Visual Merchandising, Advertising Creativity, E – Service Quality, and Perceived Value. The study uses quantitative research with the number of respondents as many as 100 respondents. The research uses primary data obtained from the dissemination of online questionnaires. The respondent was a student of the Muhammadiyah University of Greece who used or is using Spotify Premium. Later, non-probability sampling was used for sample-taking. The study found that advertising creativity and Perceived Value had a significant positive influence on purchasing decisions, while Visual Merchandising and E-Service Quality had a positive but non-significant impact on purchase decisions. The results of the study showed that the visual merchandising variable (X1) was positive but not significant, with a significance value of 0.947 for the purchasing decision variables (Y), the Advertising Creativity variable(X2) was positive and defining, with the significance of 0.012 for the purchase decision variable, the E – Service Quality (X3) had a positive but non-significant influence, and the perceived value (X4) had positive and significant influence with a significant value of 0,000 for the buying decision variabel (Y).